Habitat diversity and composition among growing wild boar (Sus scrofa L.) populations in Sweden - Olofsson, Sebastian (2015)
The wild boar (Sus scrofa L.) has expanded across Europe and Sweden in the last decades. It is a generalist species which utilizes a variety of habitats, and its presence has been shown to have both positive and negative effects for people and the landscape they are in. The abundance and increase of wild boar has previously been shown to differ between counties in Sweden, but there have been few explanations as to why. In this study, I investigated correlations between the per capita rate of change (r) among wild boar populations in Sweden and a variety of different habitats on the county level. I also investigated if fragmentation per se or in certain habitats could be associated with the wild boar’s per capita rate of change. My results show that fragmentation/diversity per se was not correlated with wild boar r. I found a negative correlation with the amount of deciduous trees in general, including oak, human activities (hunters/km2, traffic density and population density) and most agricultural variables (except oats). The results regarding clear cuts were inconclusive and would require further investigation. My results show a positive correlation between wild boar r and percentage of most types of coniferous and mixed forests, trees 21-60 years of age and the area of oats grown. The results agree with my results of fragmentation among similar habitats, where mean area, proximity to same habitat and others were positively correlated with r.